Entendimento(s) sobre o uso da resolução de problemas matemáticos : o caso de professores de matemática do 6º ao 9º ano da rede municipal de Aracaju-SE - Trindade, Deoclecia de Andrade (2012)
This article presents the results of a survey whose main theme was the teacher s understanding concerning the use of solving of mathematical problems. The aim of this research was to analyze the uses that the Mathematics teachers of the municipal schools in Aracaju do of the different types of Mathematical problems, looking for references of Solving Problems as methodology. To achieve this purpose, it was taken as a starting point a selection of Mathematical problems extracted from A Conquista da Matemática by Giovanni Jr e Castrucci (2009). These books were taken as criteria to the selection of teachers, partners of the research, since this book is adopted in sixteen out of twenty municipal schools. The selected teachers were consulted through semi-structured interviews. The theoretical support was based on the understanding defended by Onuchic (1998, 1999, 2008) and Pereira (2004 ), denominated Solving Problems as methodology; on Chapman s (1999) for the interaction symbols in the search for evidence of Solving Problems as methodology. Polya (1978), Dante (2005) and D Amore (2007) defined what typing is and what is called Mathematical Problems. From the data collected through interviews with fifteen Mathematics teachers from Aracaju, it is possible to assert that most of the teachers use Mathematical problems as a resource, after working the contents in an expository way, which are used predominantly in the problems of recognition and algorithm. However, these same teachers, when asked about the classroom management, about the teacher s and student s role, declare that they are aware that the standard problems and the application of puzzles are the most suitable to promote the interaction between student-student and student-teacher and the most appropriate to reorganize the geography of the classroom. That is, the most recommended to be taken as the starting point for the Mathematical activities and not for the fixation of the contents. Because of this, it s possible to assert that, in the case of the teachers from Aracaju, predominantly, it was just possible to identify the partial application of the aspects of an approach of the Solving Problems as methodology to work with Mathematical contents.